Towards Sustainable Cities in China Analysis and Assessment of Some Chinese Cities in 2008 - Zhao, Jingzhu; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
To promote China$1 (Bs sustainable city construction and development, this Brief has preliminarily used an assessment indicator system and development index of a sustainable city, based on a summary and analysis of the existing Sustainable City theories and practices both at home and aboard. Meanwhile, mainly based on the data from 2008, this Brief has made a tentative assessment of the development level of Sustainable City in some major Chinese cities.s
Keywords: Environmental sciences; Conservation biology; Environmental management; Environment; Environmental Management; Conservation Biology/Ecology.